The Dublin-Moscow Line: Russia and the Poetics of Home in Contemporary Irish Poetry - Kim Cheng, (ABEI Journal, 2020)
This article opens with an overview of the possibilities offered by the influence of Russian literature on Irish poetry. Subsequently, the focus shifts to Durcan’s oeuvre and the way in which Russia presents itself as an “elsewhere” which has allowed him to go beyond Ireland’s insularity and broaden his perspective. Hence, this study reveals that Durcan’s turning to Russia is an attempt to disrupt the hegemonic notion of identity according to which the links between place and self are indissoluble. Instead, it is here proposed that Russia is envisaged as an imaginary homeland where the self can be freed from Anglo-Irish tradition allowing for the shattering of myths regarding the idea of home.